MICHAEL W. MEHAFFY - Cities Alive. Jane Jacobs, Christopher Alexander, and the Roots of Urban Renaissance - Monclús Fraga, Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Michael W. Mehaffy Cities Alive. Jane Jacobs, Christopher Alexander, and the Roots of Urban Renaissance Portland, Oregon (USA): Sutasis Press, 2017. 288 pp. Softcover. Language: English. 19 € ISBN: 978-9463864046